Rancang Bangun Sistem Konversi Energi Panas Api Menjadi Energi Listrik Sebagai Alat Charger Baterai Menggunakan Termoelektrik - Rimbawati Rimbawati; Billy Prandika; Cholish Cholish (PTE FTK UIN Ar-Raniry, 2022)
The utilization of heat energy as a generator of electrical energy was conducted by using thermoelectric elements. The conversion system with Thermoelectric Generator (TEG) elements currently used in many time during the combustion process. Likewise, the fuel is sourced from charcoal, wood, coal, palm oil shells, or garbage. Based on the properties and advantages of those fuel components, this research is carried out to study and develop a system according to the capabilities of the TEG components to become a useful things. TEG components can be designed into a super mini generating system by converting fire heat into electricity. The method used in this research is a bonfire heat energy conversion system into electrical energy. The heat from the fire will be used to recharge batteries such as HT batteries, flashlights, GPS, etc. The input of the system is heat, which consisted the heat of a campfire or cooking fire. The input component itself is a converter, namely peltier. Peltier function is to convert heat energy directly into electricity. The result of this research is the output about 3.7 V. This design uses IC LM317 as a regulator to process the output voltage of the conversion system. The regulator is important to succed the battery does not overcharge and damage.